Bildatlas zum Sport im alten Ägypten. Corpus der bildlichen Quellen zu Leibesübungen, Spiel, Jagd, Tanz und verwandten Themen - Decker, Wolfgang. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1994)
This two-volume work is a comprehensive collection of the pictorial sources for sport in Pharaonic Egypt. Adopting a broad definition of sport, its scope embraces relevant cultic scenes as well as archery, charioteering and horsemanship, hunting, wrestling, open-air games and board games, acrobatics, dancing and water sports. Over 2,000 documents are given detailed descriptions, with systematic annotations relating to the place, date and content of the documents, as well as the most important secondary literature. The hieroglyphic captions are given in transcription and translation. A representative selection of the pictorial documents, accounting for approximately half of the total material, is presented in the illustrated volume. Accompanying maps classify the material by subject area with indications of their topographical distribution and chronological proximity. The publication of this corpus of materials makes available for the first time the complete pictorial tradition of a great, ancient sporting culture, the intention being to stimulate and intensify research in these fields by the provision of the basic materials.